Vejo freaks, o “estranho” me olha: aproximações entre as fotografias de Diane Arbus e a psicanálise - Guerra, Mariah Neves (2017)
This dissertation came from the questions what looks at us when we see art? and how is it possible to study it? Starting from the hypothesis of a methodological framework that brought together, in a tensioned way, knowledges of art and psychoanalysis, I chose the work of Diane Arbus, the photographer of the freaks, and the Freudian notion of “uncanny” to write this research work. This methodology was conceived from the relation between methodologies in the art field and the Freudian methodology in the text “The Uncanny” (Freud, 1919). The general objective of this research is to understand how, when I stand before a work of art, it can affect me it in what I did not even know inhabited me. In order to do so, the writing is built on the possibility and the impossibility of the relation between the Freudian “uncanny” and the photographic work of Diane Arbus. Therefore, the specific objectives are: (1) to develop what is the enigmatic “uncanny” to psychoanalysis; (2) to present the main aspects of the photographic works of Diane Arbus that affect their spectator; (3) to bring together what was developed about the “uncanny” and the photograph of Diane Arbus, to formulate how the process of affecting occurs in the subject of the unconscious when he/she stands before this art. From this research, we can see that the “uncanny” effect takes place when I look at the photos and they become “uncanny” objects and discover in me my own uncanniness. I see the freaks in the photos and they look at me in my splitting, in what I am lacking; I see the photos and they capture me. The openness induced by art occurs between what we see in it and what it looks in us, and this splitting is the lack that inhabits us.